Effect Of Using E-Filling On Quality Of Tax Reporting Services In East Java: Effect Of Using E-Filling On Quality Of Tax Reporting Services In East Java - Venantya Asmandani; Tree Setiawan Pamungkas; Rachmat Hidayat; Galih Wicaksono; Yeni Puspita; Nurcahyaning Dwi Kusumaningrum (Jurnal Mantik, 2020)
The purpose of this research is to determine the use of e-filling of the quality of tax Reporting Services partially. This research used quantitative methods and data analysis methods use SPSS software with simple regression analysis, which is used to test tested hypotheses, partially, and to see the magnitude of the coefficient. Based on the results of research and discussion can be concluded that partial use of e-filling affects the quality of the annual tax reporting Service, But the direction is negative and is proven in analysis of SPSS test results with a significance value of 0.000 < from 0.05. Increasing the use of e-filling jointly by taxpayers for annual SPT tax reporting will decrease the quality of the annual SPT tax Reporting Service, the DGP server is still not able to accommodate so many access at one time so that often occurs errors or difficult to access due to the limitations of available brandwidth.